1975
DOI: 10.3171/jns.1975.42.2.0222
|View full text |Cite
|
Sign up to set email alerts
|

Ossification of spinal arachnoid with unrelated syringomyelia

Abstract: A case demonstrating a combination of ossified spinal arachnoid and syringomyelia is reported. A plea is made for denoting the condition as "ossification of the spinal arachnoid" rather than "spinal arachnoiditis ossificans".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…The calcified arachnoid plaques were resected to variable extents due to their firm adherence to the spinal cord. In several cases, the syrinx was aspirated and a syringoperitoneal or syringopleural shunt was inserted 5,6,8. Collapse of the syrinx was noted with some postoperative clinical improvement in two of these reports 5,8.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The calcified arachnoid plaques were resected to variable extents due to their firm adherence to the spinal cord. In several cases, the syrinx was aspirated and a syringoperitoneal or syringopleural shunt was inserted 5,6,8. Collapse of the syrinx was noted with some postoperative clinical improvement in two of these reports 5,8.…”
Section: Discussionmentioning
confidence: 95%
“…Syringomyelia in the setting of AO has been hypothesized to result from vessel ischemia, CSF flow alterations, or even as a coexisting incidental finding 2,5,6. In a large study of 105 patients, Milhorat and colleagues identified 23 cases of focal intramedullary cavitation separated from the fourth ventricle by a syrinx-free segment of spinal cord 11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,15,18,21,24,27,30 They suggest that ossification in AO results from an active, progressive process. These features indicative of true ossification have been noted systematically.…”
Section: Histological Featuresmentioning
confidence: 99%
“…12,15,18,21,24,27,30 They suggest that ossification in AO results from an active, progressive process. 18 The association of ossified arachnoid with contiguous and often extensive dense fibrosis of the arachnoid suggests that ossification is the end point of arachnoiditis. 27 This possibility was suggested by Slager, 24 who observed that incidental leptomenigeal plaques in an autopsy study were calcified and not ossified.…”
Section: Histological Featuresmentioning
confidence: 99%